Variasi Fluks CO2 Udara-Laut di Perairan Pesisir Pulau Bintan - afdal; Hanif Budi Prayitno; Aán Johan Wahyudi; Suci Lastrini (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Variation of Air-Sea CO2 Fluxes in Bintan Island Coastal Water. Eastern part of Bintan coastal water plays a major role as CO2 sink. However, flux and partial pressure of CO2 (pCO2) dynamically follows spatio-temporal variability. Spatio-temporal variability of CO2 flux may shows the whole condition of Bintan Island coastal water, especially in correlation with the primary production. Systematic study on variability of CO2 flux from or to the watern column is essential to understand the whole conditions of Bintan Island coastal water. This study aims to understand the spatio-temporal variation of CO2 fluxes in Bintan Island coastal water, and the factors influencing it. This study was conducted in the eastern part of Bintan coastal water in April and August 2014. In addition, this study was also conducted in the southern and northern parts in April 2016. CO2 fluxes dynamics were calculated from pCO2 (surface water and atmosphere), temperature, salinity, and wind speed. The result showed that almost all parts of the Bintan coastal water were carbon sources during first transition season. The largest CO2 emission was observed in the northern part (4.02 ± 1.92 mmol/m2/d) followed by the southern part (2.28 ± 0.80 mmol/m2/d) and then the eastern part (0.46 ± 0.28 mmol/m2/d). The eastern part temporally turned into CO2 sink in the southwest monsoon season (-0.27 ± 0.10 mmol/m2/d). Temperature was the main factor causing spatial and temporal variability of air-sea CO2 fluxes in the Bintan coastal water. Spatially, the presence of seagrass and coral reef ecosystems causes the partial pressure of surface water CO2 in the eastern part of waters of Bintan is much lower compared to the waters of north and south Bintan, thus emitting less CO2 to the atmosphere